Optimalisasi Peran Guru dalam Proses Transformasi Pengetahuan dengan Menggunakan Media Pembelajaran Visual dan Audio Visual di MIN 3 Barito Timur - Kamaliah Kamaliah (PT. Global Pustaka Ilmiah, 2024)
Optimizing learning cannot be separated from the teacher's role in delivering learning in the classroom, including through an emphasis on process and active learning. The paradigm shift from passive learning to active learning makes the role of learning media increasingly important. Active learning requires reducing teacher dominance in the classroom. The role of the teacher is minimized and shifted by the role of learning media around the students or even learning resources which are also the source of the learning message. The development of science and technology is increasingly encouraging renewal efforts in the use of technological results in the learning process, and it is possible that the transformation of knowledge with media must be adapted to developments and demands of the times. This research aims to find out answers to the use of Visual and Audio Visual learning media to optimize the role of teachers in the knowledge transformation process. The subjects in this research were several MIN 3 East Barito teachers. This research method uses a qualitative type of research, with a case study approach where the researcher conducted a study on several MIN 3 East Barito teachers to obtain data on the use of Visual and Audio Visual learning media to optimize the teacher's role in the knowledge transformation process. The results of this research show that teachers are optimal in the learning transformation process by using visual and audio-visual learning media.